Prospects of Adaptability and Establishment of Mangroves to Achieve Carbon Capture Expansion in Korean Coastal Areas - Lee, B.; Baral, H. (Copernicus GmbH, 2023)
The research team was first tasked with finding a solution to the need for more creative ways to contribute to natural carbon capture and storage solutions to meet South Korea’s national climate-change objective of reaching net zero by 2050. It was through this, and the unique properties of Korea’s southern islands, that true mangroves and mangrove associates (semi-mangroves) were suggested as possible candidates that could promise high carbon absorption rates and adaptability to continue to provide ecosystem services under climate change. Some pre-existing native habitats of semi-mangrove species (e.g. Hibiscus hamabo, Paliurus ramosissimus) on Jeju Island had already demonstrated comparatively higher carbon absorption abilities than other broadleaf species as measured by photosynthesis rates and soil carbon storage performance. This study’s sole objective is to evaluate candidate mangrove species for their suitability for responsibly planned propagation in South Korea. This includes also evaluating their carbon uptake capabilities in order to forecast projections on the carbon storage and absorption performance of selected species. This study is an opportunity to contribute knowledge towards global emission reduction and climate-change mitigation objectives, especially, given the high concentration of highly vulnerable or at-risk populations in the Asia-Pacific.